Publishing the history play in the time of Shakespeare: stationers shaping a genre - Lidster, A (Cambridge University Press, 2022)
During the early modern period, the publication process decisively shaped the history play and its reception. Bringing together the methodologies of genre criticism and book history, this study argues that stationers have – through acts of selection and presentation – constructed some remarkably influential expectations and ideas surrounding genre. Amy Lidster boldly challenges the uncritical use of Shakespeare's Folio as a touchstone for the history play, exposing the harmful ways in which this has solidified its parameters as a genre exclusively interested in the lives of English kings. Reframing the Folio as a single example of participation in genre-making, this book illuminates the exciting and diverse range of historical pasts that were available to readers and audiences in the early modern period. Lidster invites us to reappraise the connection between plays on stage and in print, and to reposition playbooks within the historical culture and geopolitics of the book trade.